1987
DOI: 10.1164/ajrccm/136.5.1232
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vascular Tone Improves Pulmonary Gas Exchange in the Adult Respiratory Distress Syndrome

Abstract: Hemodynamics, blood gases, lung mechanics, and the distributions of ventilation-perfusion ratios (VA/Q) were studied before and after iv diltiazem, 0.5 mg/kg over 30 min, in 6 patients with pulmonary hypertension secondary to the adult respiratory distress syndrome (ARDS) ventilated with 7 to 20 cm H2O positive end-expiratory pressure (PEEP). Diltiazem decreased systemic and pulmonary arterial pressures without changes in cardiac output and in filling pressures of the heart, and with a slowing of heart rate. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…Elliot et al (6) reported persistent abnormalities of DLco as in our cases 1, 2, and 4. They also observed persistent abnormalities of oxygen transfer across the lung during exercise, a condition associated with pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Elliot et al (6) reported persistent abnormalities of DLco as in our cases 1, 2, and 4. They also observed persistent abnormalities of oxygen transfer across the lung during exercise, a condition associated with pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 66%
“…Interstitial emphysema, bullae, and pneumothorax are frequently found during the ARDS support, possibly due to barotrauma (6).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, preventing this redistribution can increase the deterioration in oxygenation [13]. Similarly, in patients with ARDS, the characteristic refractory hypoxaemia is primarily the result of intrapulmonary shunting and increased ventilation/perfusion (V9/Q9) mismatch [14], which is further exacerbated by the administration of intravenous vasodilators [15]. Thus, while the increase in Ppa attributable to HPV increases right ventricular afterload, it is a consequence of a physiological reflex designed to preserve V9/Q9 mismatch and attenuate arterial hypoxaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, several older clinical trials designed to evaluate the effects of intravenous vasodilators [e. g., nitroglycerin [17], nitroprusside [15], diltiazem [16]] found that pulmonary arterial pressure and pulmonary vascular resistance fall and PaO 2 and systemic O 2 delivery decreased as a result of increased shunt and V A /Q heterogeneity. These deleterious effects were presumed to occur secondary to the inhibition of hypoxic vasocon-943 Fig.…”
Section: Vasodilatorsmentioning
confidence: 99%
“…In humans, it has been difficult to separate vasoconstriction from the effects of PEEP although both seemingly contribute as the degree of pulmonary hypertension changes with titration of PEEP, and intravenous vasodilators reduce pulmonary vascular pressures and improve cardiac output [14,15,27,28]. Unfortunately, this beneficial hemodynamic effect is associated with worsening axygen delivery and increasing shunt (14)(15)(16) attributable to attenuation of hypoxic vasoconstriction. However, inhaled agents can circumvent this problem to some extent (see below).…”
Section: Introductionmentioning
confidence: 99%